Vertical accuracy of the USGS 3DEP program data: study cases in Fresno County and in Davis, California - Callahan, Daniel; Berber, Mike Mustafa (Boletim de Ciências Geodésicas, 2022)
3D Elevation Program (3DEP) aims to generate and disseminate high-resolution topographic elevation data from the source data products including lidar point clouds, original DEMs from which the 3DEP standard DEM datasets were produced, and additional data types produced from IfSAR collections. As such, the accuracy of 3DEP data varies due to the inconsistent quality of the source data. Hence, in order to test vertical accuracy of the current 3DEP data, two precise leveling data sets which are collected in the San Joaquin Experimental Range (SJER) in Fresno County and CalFire site in Davis, California are used as the baselines and the differences are computed. In the earlier studies, assessment of 3DEP data is accomplished using large-area elevation datasets. Nevertheless, these largearea elevation datasets are not as precise as differential (precise) leveling data sets. In this study, two relatively small sites (SJER and CalFire site) are surveyed utilizing precise leveling. These two project sites also differ from each other in terms of terrain relief and land cover. The results show that attainable precision is almost the same for 1/3 arcsecond and 1 arc-second data sets. The data sets used for CalFire site are more precise than the data sets used for SJER site. CalFire site data sets are more accurate than SJER data sets. 1 arc-second data provides as good elevation information as 1/3 arc-second data. Terrain relief and land cover are important factors on vertical accuracy coming from 3DEP data.